2017
DOI: 10.1371/journal.pone.0179383
|View full text |Cite
|
Sign up to set email alerts
|

Elevated sodium leads to the increased expression of HSP60 and induces apoptosis in HUVECs

Abstract: Atherosclerosis is the leading cause of death in the world. We have previously shown that expression of heat shock protein 60 (HSP60) on the surface of endothelial cells is the main cause of initiating the disease as it acts as a T cell auto-antigen and can be triggered by classical atherosclerosis risk factors, such as infection (e.g. Chlamydia pneumoniae), chemical stress (smoking, oxygen radicals, drugs), physical insult (heat, shear blood flow) and inflammation (inflammatory cytokines, lipopolysaccharide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 74 publications
1
47
1
Order By: Relevance
“…(37) Additionally, in endothelial cells, the expression of HSP60 is a marker of chemical stress such as from smoking or free radicals, and increases the risk of atherosclerosis. (35) In contrast to our results, Kleinridders et al (38) reported that mitochondrial dysfunction is induced by downregulation of HSP60 in diabetic mice, and ROS production and insulin resistance are increased. In our previous study, we found that mitochondria accumulate in neurite beading regions (18) and induce superoxide production in hydrogen peroxide-treated neuronal cells.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…(37) Additionally, in endothelial cells, the expression of HSP60 is a marker of chemical stress such as from smoking or free radicals, and increases the risk of atherosclerosis. (35) In contrast to our results, Kleinridders et al (38) reported that mitochondrial dysfunction is induced by downregulation of HSP60 in diabetic mice, and ROS production and insulin resistance are increased. In our previous study, we found that mitochondria accumulate in neurite beading regions (18) and induce superoxide production in hydrogen peroxide-treated neuronal cells.…”
Section: Discussioncontrasting
confidence: 99%
“…(34) Much of the literature on HSP60 is related to immune diseases. (35) However, several studies have demonstrated a relationship between changes in HSP60 and neurodegenerative disorders. (34,36,37) HSP60 binds to amyloid precursor protein and beta-amyloid, and accumulates in the mitochondria of AD transgenic mice brains.…”
Section: Discussionmentioning
confidence: 99%
“…An outline was drawn around each cell (100 cells per sample) and the area, integrated density and mean gray value were measured along with adjacent background readings. Next, corrected total cell fluorescence (CTCF) = integrated density (area of selected cell × mean fluorescence of background readings) was calculated as described previously [68].…”
Section: Immunofluorescencementioning
confidence: 99%
“…Cytosolic HSP60 promotes the activation of procaspase-3 through cytochrome c and dATP in an ATP-dependent manner, suggesting a pro-apoptotic function [15]. Elevated sodium chloride concentration induces apoptosis in human umbilical vein endothelial cells and induces cytosolic and surface expression of HSP60 as well, which triggers autoimmune responses and leads to atherosclerosis [17]. However, in this case, the pro-or anti-apoptotic function of cytosolic HSP60 has not been clearly characterized.…”
Section: Dual Functions Of Hsp60 In Cytosolmentioning
confidence: 99%
“…The contradictory role of cytosolic HSP60 on the regulation of apoptosis has been demonstrated in different studies [14,15]. HSP60 in the cytosol has a pro-survival function, while it also participates in the apoptosis process upon cell death stimuli [15][16][17].…”
Section: Introductionmentioning
confidence: 99%